O impacto transformador do Protocolo Facultativo à Convenção sobre a Eliminação de Todas as Formas de Discriminação contra a Mulher na proteção dos direitos humanos à saúde materna: o caso Alyne da Silva Pimentel Teixeira - Giese, Núbia Caroline Tavares Costa (2020)
The Convention on the Elimination of All Forms of Discrimination Against Women or CEDAW was the second international treaty incorporated into the Special System for the Protection of Human Rights in 1979. This system is constituted by several international conventions with the purpose of safeguarding the rights of vulnerable groups, respecting their specificities, particularities and providing means to eliminate the historical disparities that have made them inferior, excluded and segregated, denying them the full condition of subject of rights. In this tone that CEDAW was conceived with two main objectives: to promote the rights of women in the pursuit of gender equality and to repress any discrimination by States Parties against women. Under this approach, CEDAW envisaged a Committee that initially intended to monitor and review the periodic reports submitted by the States Parties to formulate suggestions and recommendations for adaptation to the Convention. However, there was a need for more resolute action that could vehemently repress and reject any and all doctrines of superiority based on the differences between men and women. Thus, the CEDAW Committee together with the Commission on the Status of Women (CSW) recommended the elaboration of the Optional Protocol to CEDAW, which expanded the Committee's functions for receiving petitions and investigating complaints about violations of women's rights. Based on the above, the purpose of this research is to analyze the theoretical and practical foundations of Alyne da Silva Pimentel Teixeira case versus Brazil submitted to the Committee for violation of maternal health right, an essential component of reproductive rights. And, with that, extract what were the impacts that the decision of the CEDAW Committee, which condemned Brazil in 2011 for the preventable maternal death of Alyne Pimentel, contributed to change the Brazilian health system, from the perspective of protecting maternal health